The Role And Significance Of Mirzo Bedil's Creative Path In The Development Of Philosophical Prose - Jamshid Tavmuradov (Academia One Publishing, 2026)
This article explores the role and significance of Mirzo Bedil’s creative path in the development of philosophical thought, with particular emphasis on his contribution to the intellectual tradition of the Islamic East. The study analyzes Bedil’s works as a synthesis of philosophical reflection, poetic expression, and Sufi metaphysics, through which he articulated complex ideas about human existence, knowledge, morality, and spiritual perfection. Special attention is given to Bedil’s worldview as an original form of intellectual inquiry, where rational argument, symbolic imagery, and mystical interpretation coexist within a unified conceptual system. The article highlights Bedil’s influence on the formation of ethical and anthropological perspectives in Persian-Tajik and Central Asian literary-philosophical culture. It also examines how Bedil’s philosophical ideas contributed to the continuity of classical thought while offering new interpretive possibilities for understanding the human being, the self, and the relationship between the material and spiritual dimensions of reality.
Keywords: Mirzo Bedil; philosophical thought; Sufi metaphysics